1999
DOI: 10.1074/jbc.274.9.5271
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of L-selectin-mediated Leukocyte Rolling by Synthetic Glycoprotein Mimics

Abstract: Synthetic carbohydrate and glycoprotein mimics displaying sulfated saccharide residues have been assayed for their L-selectin inhibitory properties under static and flow conditions. Polymers displaying the L-selectin recognition epitopes 3,6-disulfo Lewis x(Glc) (3-O-SO 3 -Gal␤1␣4(Fuc␣1␣3)-6-O-SO 3 -Glc␤-OR) and 3,6-disulfo Lewis x(Glc) (3,6-di-O-SO 3 -Gal␤1␣4(Fuc␣1␣3)Glc␤-OR) both inhibit L-selectin binding to heparin under static, cell-free binding conditions with similar efficacies. Under conditions of shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 95 publications
2
77
0
Order By: Relevance
“…Physiological L-selectin ligands typically present multiple copies of derivatives of the sulfated sialyl Lewis × antigen (sLe × ); synthetic multivalent ligands that display these and related carbohydrate epitopes have been shown to be effective selectin ligands. [248][249][250][251][252][253] Multivalency, therefore, may be an important determinant of L-selectin function in vivo. Experiments using synthetic multivalent ligands have begun to reveal the importance of multivalency and stoichiometry of selectin-ligand clusters for L-selectin recognition.…”
Section: 3a B Cell Antigenmentioning
confidence: 99%
“…Physiological L-selectin ligands typically present multiple copies of derivatives of the sulfated sialyl Lewis × antigen (sLe × ); synthetic multivalent ligands that display these and related carbohydrate epitopes have been shown to be effective selectin ligands. [248][249][250][251][252][253] Multivalency, therefore, may be an important determinant of L-selectin function in vivo. Experiments using synthetic multivalent ligands have begun to reveal the importance of multivalency and stoichiometry of selectin-ligand clusters for L-selectin recognition.…”
Section: 3a B Cell Antigenmentioning
confidence: 99%
“…Given that L-selectin functions in the dynamic processes of tethering and rolling of lymphocytes, a complete analysis of 6-sulfo-sLe X must examine the contribution of each modification (including sulfation) to kinetic constants as well as to the overall equilibrium constant. A previous study has shown that sulfated Le X derivatives can exhibit very different inhibitory activities against L-selectin depending upon whether equilibrium or flow chamber assays are used (37).…”
Section: Fig 2 Binding Of L-selectin/igm To Sulfated Lactose Neoglymentioning
confidence: 99%
“…Furthermore, Kannagi and coworkers (33, 34) have described 6-sulfo-sLe X -reactive antibodies that stain HEVs and inhibit L-selectin binding to HEVs. With respect to the contribution of Gal-6-SO 4 , several groups have reported that this modification of sLe X or of sLe X mimetics either enhances or does not affect L-selectin binding (29,30,(35)(36)(37). In marked contrast, Feizi and co-workers found that this modification eliminates binding to L-selectin (28, 38).…”
mentioning
confidence: 99%
“…The second combined effect is the polymeric effect of the PV6Gna engaging ASGPR in multivalent binding on the hepatocyte cell surface. Multivalent synthetic glycoprotein inhibits L-selectin-mediated leukocyte rolling more effectively than the corresponding monomer (7). Several reports have demonstrated a multivalent effect of ligands for an optimum recognition to the structure of ASGPRs (49,50).…”
Section: Table I Inhibition Of Hepatocyte Adhesion To the Pv6gna Surfmentioning
confidence: 99%
“…Multivalent glycopolymer ligands have been designed for clustering of L-selectin leading to the activation of the leukocyte cell surface and the inhibition of L-selectin-mediated leukocyte rolling (6,7). Interaction between the carbohydrate and the carbohydrate-binding proteins (CBPs) 1 is achieved through hydrogen bonding of the hydroxyl group of the carbohydrate to the polar amino acid side chain of the protein, including the packing of a hydrophobic sugar face against the aromatic amino acid side chain of the protein (8).…”
mentioning
confidence: 99%